2011
DOI: 10.1258/jtt.2011.110211
|View full text |Cite
|
Sign up to set email alerts
|

Teleconsultation: changes in technology and costs over a 12-year period

Abstract: In our previous study, in 1997, we evaluated the cost of teleconsultations in a primary care centre compared with the cost of the conventional alternative, travelling to the hospital. The results showed that teleconsultations were cheaper than patient travel when the annual workload was more than 110 patients in ophthalmology and 115 patients in dermatology. Using the same method of analysis for 2009 data showed that cost savings would occur if the annual workload was 20 patients in ophthalmology and 17 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“… 19 Examinations through teleophthalmology were shown to be less expensive than conventional in-person examinations. 20 A study showed that screening for DR in a community health center was 35% less costly when telemedicine was used rather than direct observation. 21 Use of telemedicine screening for DR among populations in underdeveloped rural areas showed cost efficiency, but the expense of maintaining remote imaging facilities in such circumstances may render annual testing economically impractical.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Examinations through teleophthalmology were shown to be less expensive than conventional in-person examinations. 20 A study showed that screening for DR in a community health center was 35% less costly when telemedicine was used rather than direct observation. 21 Use of telemedicine screening for DR among populations in underdeveloped rural areas showed cost efficiency, but the expense of maintaining remote imaging facilities in such circumstances may render annual testing economically impractical.…”
Section: Discussionmentioning
confidence: 99%
“…Equally important considerations are software, information technology support, administration costs, training, licensing fees, software updates, and the time available to provide the services of both originating and distant site providers. 9,125 Less easily quantified costs must also be considered. For example, one Australian group found more time was needed for a telemedicine visit than for an in-person visit, although other providers with more extensive experience have not found this to be the case.…”
Section: Financial Impact Of Telemedicine: Cost Evaluation and mentioning
confidence: 99%
“…Our interviews with patients con rmed that our program was successful at overcoming both of these barriers. Although there are start-up costs for purchasing equipment, tele-ophthalmology has been shown to save costs to the healthcare system and patients in the longterm, and is therefore a more nancially sustainable alternative than hospital-based screening for many remote lower-resource settings [14][15][16].…”
Section: Discussionmentioning
confidence: 99%